Attenuation of neurological deficit by a novel ethanolamine derivative in rats after brain trauma - Sysoev YI; Uzuegbunam BC; Okovityi SV (Dove Medical Press, 2019)
Yuriy Igorevich Sysoev,1,2 Bright Chukwunwike Uzuegbunam,1 Sergey Vladimirovich Okovityi11Department of Pharmacology and Clinical Pharmacology, Saint-Petersburg State Chemical-Pharmaceutical University, St. Petersburg, Russia; 2Institute of Translational Biomedicine (ITBM), Saint-Peterburg State University, St. Petersburg, RussiaObjectives: To prove that our novel ethanolamine derivative (FDES) can normalize overall movement and exploratory activity of rats with traumatic brain injury (TBI) owing to its peculiar properties.Materials and methods: TBI was modeled using controlled cortical impact injury (CCI) model method. The resulting neurological deficit, efficacy of the novel agent and other reference agents used were assayed in tests which evaluated overall movements and exploratory behavior of the rats. Finally, scopolamine in equimolar dose was used to estimate the role of cholinergic system in the efficacy of our agent. The tests included: limb-placing, open field, elevated plus maze, cylinder, and beam walking tests.Results: Intraperitoneal administration of FDES at a dose of 10 mg/kg led to improvement of fore- and hind-limb functions of rats with traumatic brain injury as was shown in “Limb placing”, “Open field” “Cylinder” and “Beam walking” tests. The new agent had no effects on traumatized rats behavior in the “Elevated Plus Maze” test. Simultaneous co-administration of scopolamine with FDES reduced the beneficial effects of the latter in rats with trauma.Conclusion: The neuroprotective effects of new agent were manifested in the reduction of motor deficiencies, and exploratory activity in the CCI model rats. In comparison with choline alfoscerate and citicoline, FDES showed more beneficial effects as were observed in most of the tests, and did not negatively influence the traumatized rats psychologically. Notably, it is possible that the neuroprotective influence of the new agent is mediated by its actions on the cholinergic system.Keywords: traumatic brain injury, neuroprotective drugs, ethanolamine derivatives